Shape memory alloy engineering : for aerospace, structural and biomedical applications - Lecce, Leonardo; Concilio, Antonio; Ameduri, Salvatore (Butterworth-Heinemann, 2015)
This book ntroduces materials, mechanical, and aerospace engineers to shape memory alloys (SMAs), providing a unique perspective that combines fundamental theory with new approaches to design and modeling of actual SMAs as compact and inexpensive actuators for use in aerospace and other applications. Readers will gain an understanding of the intrinsic properties of SMAs and their characteristic state diagrams, allowing them to design innovative compact actuation systems for applications from aerospace and aeronautics to ships, cars, and trucks. The book realistically discusses both the potential of these fascinating materials as well as their limitations in everyday life, and how to overcome some of those limitations in order to achieve proper design of useful SMA mechanisms. It provides detailed examples on design procedures and optimization of SMA-based actuation systems for real cases, from specs to verification lab tests on physical demonstrators. --